2020
DOI: 10.5398/tasj.2020.43.3.227
|View full text |Cite
|
Sign up to set email alerts
|

Performances and Egg Quality of Laying Ducks Fed Diets Containing Cassava (Manihot esculenta Crantz) Leaf Meal and Golden Snail (Pomacea canaliculata)

Abstract: The objective of this study was to evaluate the effect of feeding cassava leaf meal and golden snail on performances, chemical, and physical qualities of local duck egg. The experiment used 180 Pajajaran laying ducks of 20 weeks of age and was offered dietary treatments up to 26 weeks of age. The experiment was conducted in a completely randomized design with a 3 x 2 factorial arrangement. The first factor was the treatment of cassava leaf meal consisted of 3 levels, i.e., 0%, 5%, and 10%. The second factor wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Phytogenic feed additives obtained from herbal plant extracts are commonly used in poultry, particularly in laying hens. Phytogenics, also known as phytobiotics, have beneficial effects on gut health and performance due to the presence of bioactive compounds such as polyphenols with antimicrobial, antioxidant, immunomodulatory, and anti-inflammatory properties [ 1 , 2 ]. Polyphenol compounds are the most widely produced plant bioactive compounds that serve to protect plants from the pests and UV radiation that can be found in plant parts, including the fruit, seeds, roots, bark, and leaves [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phytogenic feed additives obtained from herbal plant extracts are commonly used in poultry, particularly in laying hens. Phytogenics, also known as phytobiotics, have beneficial effects on gut health and performance due to the presence of bioactive compounds such as polyphenols with antimicrobial, antioxidant, immunomodulatory, and anti-inflammatory properties [ 1 , 2 ]. Polyphenol compounds are the most widely produced plant bioactive compounds that serve to protect plants from the pests and UV radiation that can be found in plant parts, including the fruit, seeds, roots, bark, and leaves [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some promising productive performance results, which vary according to their nutritional composition and their level of incorporation in diets, have been reported. Houndonougbo et al (2012), Galon et al (2017) and Sumiati et al (2020) reported that M. esculenta leaf improved egg production performances at 5% inclusion level in the feed. Similarly, Ngueda et al (2020) indicated that the effect of various levels of M.…”
Section: Introductionmentioning
confidence: 99%
“…Houndonougbo et al (2012), Galon et al (2017) and Sumiati et al. (2020) reported that M. esculenta leaf improved egg production performances at 5% inclusion level in the feed. Similarly, Ngueda et al.…”
Section: Introductionmentioning
confidence: 99%
“…Akruyek and Okure [ 2 ] mentioned that after the age of 50 weeks, egg production decreases, and egg weight increases; however, the weight and thickness of the eggshell, the pH of albumen and yolk, yolk index, and albumen index decrease. Duck eggs contain complete nutrition, that is, protein 10.7% [ 3 ], omega-3 and omega-6 [ 4 ], cholesterol 2.04 mg/g, and fat 31.88% [ 5 ]. Some consumers have an issue with the high content of cholesterol in duck eggs.…”
Section: Introductionmentioning
confidence: 99%